2014
DOI: 10.1021/ac403469y
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Huanglongbing Disease Using Differential Mobility Spectrometry

Abstract: The viability of the multibillion dollar global citrus industry is threatened by the "green menace", citrus greening disease (Huanglongbing, HLB), caused by the bacterial pathogen Candidatus Liberibacter. The long asymptomatic stage of HLB makes it challenging to detect emerging regional infections early to limit disease spread. We have established a novel method of disease detection based on chemical analysis of released volatile organic compounds (VOCs) that emanate from infected trees. We found that the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 42 publications
3
91
0
1
Order By: Relevance
“…More than 40 compounds were identified that can be used as biomarkers of disease, potentially before visual or non-volatile chemical traits can be observed. A similar volatile biomarker-discovery study was described for Citrus sinensis infection with Candidatus liberibacter (Aksenov et al, 2014), highlighting the potential use of chemical biomarkers of disease with non-destructive sampling during the growing season.…”
Section: Example Studies That Utilize Ms-metabolomics Workflows In Plmentioning
confidence: 60%
“…More than 40 compounds were identified that can be used as biomarkers of disease, potentially before visual or non-volatile chemical traits can be observed. A similar volatile biomarker-discovery study was described for Citrus sinensis infection with Candidatus liberibacter (Aksenov et al, 2014), highlighting the potential use of chemical biomarkers of disease with non-destructive sampling during the growing season.…”
Section: Example Studies That Utilize Ms-metabolomics Workflows In Plmentioning
confidence: 60%
“…The results showed that the sensor clearly highlighted the starch accumulation in the HLB-infected leaf and differentiated it from visually analogous symptoms of zinc deficiency (Pourreza et al 2015). Aksenov et al (2014) developed a method of disease detection based on chemical analysis of released volatile organic compounds (VOCs) that emanate from infected trees. They found that the biomarkers' "fingerprint" is specific to the causal pathogen and could be interpreted using analytical methods, such as gas chromatographymass spectrometry (GC-MS) and gas chromatographydifferential mobility spectrometry (GC-DMS).…”
Section: Spectroscopic and Imaging Techniques For Hlb Disease Detectionmentioning
confidence: 99%
“…Pyrolysis helps to provide biomarker liberation from bacteria/endospores (Cheung et al 2009; Eiceman et al 2006; Krebs et al 2006b; Prasad et al 2008), which can then be separated and detected by DMS. Gas chromatography allows for a modest pre-separation of a very complex mixture before additional DMS separation and detection (Aksenov et al 2014; Arasaradnam et al 2014a; Arasaradnam et al 2014b; Basanta et al 2010; Covington et al 2013; Rutolo et al 2014; Schivo et al 2013). The data sets that result are usually extremely complex and multi-dimensional, with some data features being very abundant but perhaps unimportant, and other data features having small abundance but high significance.…”
Section: Introductionmentioning
confidence: 99%
“…Linear discriminant analysis (Covington et al 2013; Rutolo et al 2014) and Fisher discriminant analysis (Arasaradnam et al 2014b) have been used as classification methods for biological data as well. Partial least squares (Aksenov et al 2014; Cheung et al 2009) is well established and a valuable method to classify groups of GC/DMS data, and our software system has initially included this analytical tool for model building. A description of our software applying this technique (PCA, PLS, background correction and smoothing) to data that have been previously published (Aksenov et al 2014) is presented as an illustrative example throughout this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation